Can a More User‐Friendly Medicare Plan Finder Improve Consumers’ Selection of Medicare Plans? - Martino, Steven C. (Health Serv Res, 2016)
OBJECTIVE: To evaluate the efficacy for consumers of two potential enhancements to the Medicare Plan Finder (MPF)—a simplified data display and a “quick links” home page designed to match the specific tasks that users seek to accomplish on the MPF. DATA SOURCES/STUDY SETTING: Participants (N = 641) were seniors and adult caregivers of seniors who were recruited from a national online panel. Participants browsed a simulated version of the MPF, made a hypothetical plan choice, and reported on their experience. STUDY DESIGN: Participants were randomly assigned to one of eight conditions in a fully factorial design: 2 home pages (quick links, current MPF home page) × 2 data displays (simplified, current MPF display) × 2 plan types (stand‐alone prescription drug plan [PDP], Medicare Advantage plan with prescription drug coverage [MA‐PD]). PRINCIPAL FINDINGS: The quick links page resulted in more favorable perceptions of the MPF, improved users’ understanding of the information, and increased the probability of choosing the objectively best plan. The simplified data display resulted in a more favorable evaluation of the website, better comprehension of the displayed information, and, among those choosing a PDP only, an increased probability of choosing the best plan. CONCLUSIONS: Design enhancements could markedly improve average website users’ understanding, ability to use, and experience of using the MPF.